Pathways to child and adolescent psychiatric care in the division of child and adolescent psychiatry at Red Cross Children's Hospital - Hurrissa, Birke Anbesse (Division of Child and Adolescent Psychiatry, 2015)
Objective: To document the routes taken by patients to reach the Division of Child and Adolescent Psychiatry (DCAP) at Red Cross Children’s Hospital and to identify the factors that are associated with delay in gaining access to care.